2017
DOI: 10.1016/j.vaccine.2017.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events following quadrivalent meningococcal CRM-conjugate vaccine (Menveo®) reported to the Vaccine Adverse Event Reporting system (VAERS), 2010–2015

Abstract: Background Limited data are available describing the post-licensure safety of meningococcal vaccines, including Menveo®. We reviewed reports of adverse events (AEs) to the Vaccine Adverse Event Reporting System (VAERS) to assess safety in all age groups. Methods VAERS is a national spontaneous vaccine safety surveillance system co-administered by the Centers for Disease Control and Prevention and the US Food and Drug Administration. We searched the VAERS database for US reports of adverse events in persons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 19 publications
1
31
0
1
Order By: Relevance
“…The safety profile observed for 9vHPV is consistent with data from the vaccine's prelicensure clinical trials and is similar to postlicensure safety monitoring data for 4vHPV and bivalent HPV vaccine and for other vaccines administered in this age group (eg, tetanus, diphtheria, and acellular pertussis; meningococcal conjugate; and influenza vaccines). 7,[36][37][38][39] For 9vHPV, 97.4% of reports to the VAERS were classified as nonserious (versus 94.2% for 4vHPV); crude AE reporting rates for all reports and serious reports were 259 and 7 reports per million doses distributed, respectively (versus 327 and 19 reports per million, respectively, for 4vHPV); and the most frequently reported AEs (dizziness, syncope, headache, nausea, and injection site reactions) were similar to those observed for 4vHPV. 7 VAERS is a critical early warning system to detect possible safety problems in US-licensed vaccines and is a key component of the US vaccine safety monitoring infrastructure.…”
Section: Discussionmentioning
confidence: 79%
“…The safety profile observed for 9vHPV is consistent with data from the vaccine's prelicensure clinical trials and is similar to postlicensure safety monitoring data for 4vHPV and bivalent HPV vaccine and for other vaccines administered in this age group (eg, tetanus, diphtheria, and acellular pertussis; meningococcal conjugate; and influenza vaccines). 7,[36][37][38][39] For 9vHPV, 97.4% of reports to the VAERS were classified as nonserious (versus 94.2% for 4vHPV); crude AE reporting rates for all reports and serious reports were 259 and 7 reports per million doses distributed, respectively (versus 327 and 19 reports per million, respectively, for 4vHPV); and the most frequently reported AEs (dizziness, syncope, headache, nausea, and injection site reactions) were similar to those observed for 4vHPV. 7 VAERS is a critical early warning system to detect possible safety problems in US-licensed vaccines and is a key component of the US vaccine safety monitoring infrastructure.…”
Section: Discussionmentioning
confidence: 79%
“…One study observed an increased risk for Bell's palsy among adolescents after MenACWY-CRM vaccination, although this was based on a small number of cases and the importance of this finding is uncertain (138). No additional safety concerns have been identified in postlicensure surveillance, although administration errors appear more common than with other vaccines, predominantly because of the need to reconstitute the vaccine using lyophilized and liquid components (139,140).…”
Section: Menacwy-crm (Menveo)mentioning
confidence: 99%
“…Performing the Causality Assessment, the relation was "consistent causal association to immunization". 35…”
Section: Casementioning
confidence: 99%